EXCIPIENTS SELECTION AND CHARACTERIZATION FOR «RALITIN» GEL FOR ORAL ADMINISTRATION - E. Y. Zagorulko; A. A. Teslev (Разработка и регистрация лекарственных средств, 2019)
The results of the investigation on the excipients selection for "Ralitin" gel for oral administration containing Matricaria flowers extractives (sum of flavonoids, essential oil) are presented in the article. The extractive was obtained using previously developed ultrasonic extraction technology. Gel compositions of the extractive with sodium carboxymethyl cellulose (Na-CMC), carboxymethyl cellulose (CMC), agar, carbomer, xanthan gum, gum arabic, apple pectin and mixtures thereof (Na-CMC - gum arabic, CMC - gum arabic, apple pectin - agar, xanthan gum - gum arabic) were studied. Studies on the selection of flavouring agents (orange, raspberry, banana, coconut) and commercially available sweeteners containing sodium saccharinate, sodium cyclamate, fructose, stevioside, stevia leaf extract, inulin, sucralose, and erythritol were carried out. Use of citric acid in the gel compositions at various concentrations as an acidulant and a pH regulator was investigated. The appearance, pH 5% aqueous solution, stability at elevated temperature (40 °C), rheological characteristics: dynamic viscosity (at a given shear rate of 50 s-1) and viscosity vs. shear rate (the shear rate measurement range was between 10 s-1 and 200 s-1 and vice versa) were evaluated for the gel compositions. The organoleptic characteristics of the gel compositions were evaluated using the profile method and the evaluation method with letter and numerical indexes by I. A. Egorov. The stability, aggregative stability, rheological characteristics, flavonoids release ("Dissolution" test), taste profile were determined for the developed gel composition for oral administration. The aggregative stability of "Ralitin" gel was studied under conditions of natural storage (20 ºС) and at elevated temperature (40 ºC). It was established that the value of the kinetic stability coefficient of the gel samples did not change during 6 months of storage and remained equal to 0, which allows considering the system as aggregatively stable. In examination of the sum of flavonoids release, it was found that about 90% of the total amount of flavonoids was released from "Ralitin" gel into the dissolution medium during the first 5 minutes. In studying stability of the gel during storage by the "accelerated aging" method, it was established that the obtained gel is stable during the entire experimental shelf life (2 years). "Ralitin" gel on the basis of Matricaria flowers extractive contains Na-CMC as a gelation agent, sorbic acid as a preservative, and flavouring agents - sucralose with inulin, banana flavour, and citric acid. Thus, the excipients selection for the formulation of "Ralitin" gel for oral administration has been carried out. Rheological characteristics, dissolution profile and organoleptic properties of the resulting gel are acceptable.